2016
DOI: 10.1007/s11442-016-1355-3
|View full text |Cite
|
Sign up to set email alerts
|

HSR mechanisms and effects on the spatial structure of regional tourism in China

Abstract: Chinese railway has entered the "HSR era", while the structure of "four vertical and four horizontal" railways for transit passengers is almost completed. Taking the Beijing-Shanghai High-Speed Rail (hereinafter referred to as HSR) as an example, this paper first explores HSR's effects on the spatial structure of regional tourist flows using the social network analysis. Next, it notes changes in the accessibility of regional transportation. After analyzing the factors including initial endowment of regional to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…For the small-and medium-sized cities, it was not significant, which is similar to the result of Shen et al that the impetus of Spanish HSR on urban growth was more obvious in big cities than in small cities (Shen et al, 2013). This may be because accessibility of big cities was improved drastically with frequent HSR runs (Jiao et al, 2017), and just due to the emergence of HSR, big cities attracted population, capital, and other economic factors from other cities more conveniently than before by their advantages (Wang et al, 2016).…”
Section: Heterogeneity Of Hsr Impact On Ulesupporting
confidence: 74%
See 2 more Smart Citations
“…For the small-and medium-sized cities, it was not significant, which is similar to the result of Shen et al that the impetus of Spanish HSR on urban growth was more obvious in big cities than in small cities (Shen et al, 2013). This may be because accessibility of big cities was improved drastically with frequent HSR runs (Jiao et al, 2017), and just due to the emergence of HSR, big cities attracted population, capital, and other economic factors from other cities more conveniently than before by their advantages (Wang et al, 2016).…”
Section: Heterogeneity Of Hsr Impact On Ulesupporting
confidence: 74%
“…Compared with big cities, because of lack of driving forces, small cities were more dependent on HSR station location with respect to ULE. The ability of factor conglomeration of big cities was higher than that of small cities (Wang et al, 2016), and they did not completely depend on HSR station location to drive urban growth; therefore, HSR station distance exerted negative effect on ULUI only for small cities. observed that for the central region cities and small cities, HSR station distance exerted a negative effect on ULUI, which should be regulated emphatically.…”
Section: General Impactmentioning
confidence: 83%
See 1 more Smart Citation
“…Others utilized this theory to develop theoretical concepts and quantification methods of tourist destinations' life cycles (Lundtorp and Wanhill, 2001;Shao and Gao, 2006;Yang, 2009;Zhang and Sun, 2012;Salvador, 2016). As the study of tourism evolution developed further, scholars gradually extended their attention to the development of tourist destinations to scenic spots, service facilities, transportation elements, land use, and other aspects while acknowledging that the traditional life cycle theory was no longer sufficient to explain evolutionary processes and mechanisms (Jin et al, 2009;Wang et al, 2011;Ji et al, 2012;Geng and Song, 2013;Yang and Lu, 2013;Liao et al, 2014;Xi et al, 2015;Wang et al, 2016;Pagliara et al, 2017;Hernandez et al, 2017;Liu and Li, 2018). The advances of system sciences allowed scholars to successively apply general system theory, dissipative structure theory, and system dynamics theory to the study of tourist destination evolution in order to explain evolutionary processes and mechanisms based on the perspective of the system and explore the characteristics of tourist destination systems, such as integrity, organicity, dynamics, and non-equilibrium (Yang et al, 2009;Lu and Bao, 2010;Liu et al, 2013;Olmedo and Mateos, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Huang Ai-lian (2011) [2], Xiao Yan-fei (2013) [3], Wang De-gen (2015) [4] build a double logarithm model, use the new economic geography model, the grey prediction model, the social survey questionnaire, GIS and social network analysis method, to discuss the influence of Wuhan-Guangzhou HSR and Beijing-Shanghai HSR on the development of tourism and producer services industry in their neighboring areas, put forward the contribution of the diffusion and agglomeration effects of High-speed railway on the regional tourism and service From the qualitative and macro point of view, from the perspective of economics, the new geography perspective, most of these studies explore the impact of transportation on the regional tourism economy and put forward the countermeasures for the development of regional tourism economy in the era of High-speed railway. This paper constructs the index reflecting the social, economic and tourism development of tourism economic zone along High-speed …”
mentioning
confidence: 99%